Application of spectrophotometry in novel simultaneous dissolution profiling of a single pill triple therapy of amlodipine, perindopril and indapamide; whiteness evaluation - Aya T. Soudi (BMC Chemistry)
Abstract Simple, diverse univariate spectrophotometric methods were developed and validated for the determination of amlodipine besylate (AM), perindopril arginine (PE), and indapamide (ID). The first method involved direct measurement of AM absorbance at 365 nm within a concentration range of 2.00–40.00 µg/mL, where PE and ID exhibited no spectral interference. To eliminate the contribution of AM from the ternary mixture, its spectrum was divided by a reference spectrum of AM (12 µg/mL), followed by mathematical subtraction of the resulting constant. The spectrum was then multiplied by the AM divisor to yield a corrected spectrum of the PE and ID binary mixture, allowing their quantification. Various approaches were used to quantify both drugs, including measurement of their second (2DD) and first derivative (1DD) spectra at 231.30 nm and 251.00 nm, respectively. Additionally, the ratio difference (RD) technique and dual wavelength (DW) method were employed. The concentration ranges for PE and ID were 5.00–100.00 µg/mL and 1.00–20.00 µg/mL, respectively. Among these methods, the DW technique was the simplest, so it was chosen for dissolution monitoring of PE and ID. These methods were successfully applied to determine AM, PE, and ID in bulk powder, as well as in Triplixam® tablets, without interference from excipients and in different used dissolution media. The whiteness of the method was evaluated, demonstrating its excellent environmental, analytical and practical efficiency.